Pre-service EFL’ Teachers’ perception of multilingualism and multilingual education - Syarifah Safira Syahrani Al’Aidid; Herri Mulyono (Universitas Sulawesi Barat, 2023)
The objective of the current study was to investigate the perception of pre-service teachers in Indonesia regarding multilingualism and multilingual in education, outlining the benefits of multilingualism in teaching. In this paper, the term of multilingualism was employed to reflect the ability to speak more than one language competently. To this end, a total of 250 pre-service English as a Foreign Language (EFL) teachers were invited to complete the study; however, only 203 responses were sufficient to be analysed using Rasch Modeling. These responses consisted of 159 female and 44 male pre-service teachers; and 164 pre-service teachers were from private universities and the rests were public university. The findings of this study indicate that a majority of pre-service teachers view multilingualism as beneficial to both their students and themselves. Most participants perceived that multilingualism could facilitate student learning of a new language, help develop their cognitive and communicative skills, and provide them with familiarity with additional languages for easier communication